2014
DOI: 10.1371/journal.pone.0099329
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Quantify within Dive Foraging Behaviour in Marine Predators

Abstract: Studies on diving behaviour classically divide a dive into three phases: the descent, bottom and ascent phases, with foraging assumed to occur during the bottom phase. The greater complexity of dive revealed through modern, high resolution data highlights the need to re-assess this approach and to consider a larger number of phases within individual dives. Two southern elephant seals (SES) were fitted with a head mounted Time Depth Recorder (TDR) and an accelerometer from which prey capture attempts were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 64 publications
8
90
0
Order By: Relevance
“…One adult female Weddell seal was captured in February 2008 after its annual moult at Dumont D'Urville (66°40′ S, 140°00 E) (length 230 cm). Similar capture and tagging procedures were used for both species and are fully described in [21]. A TDR combined with an accelerometer (TDR Mk 10 X, Wildlife Computers) and a TDR (Mk 10, Wildlife Computers) was head-glued to the SES and to the back of the Weddell seal, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…One adult female Weddell seal was captured in February 2008 after its annual moult at Dumont D'Urville (66°40′ S, 140°00 E) (length 230 cm). Similar capture and tagging procedures were used for both species and are fully described in [21]. A TDR combined with an accelerometer (TDR Mk 10 X, Wildlife Computers) and a TDR (Mk 10, Wildlife Computers) was head-glued to the SES and to the back of the Weddell seal, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, Dragon et al [14] and Thums et al [20] demonstrated that deep foraging dives in southern elephant seals (SES) were associated with high descent/ascent rates, but relatively short bottom times. Moreover, a recent study on a Weddell seal and SES demonstrated that the three-phase model of diving behaviour (descent, bottom and ascent) is overly simplistic and that using the bottom time only as an index of foraging effort can be misleading and inaccurate, because: (1) intensification of the foraging effort could occur several times within a dive and (2) this may not occur necessarily during the bottom phase [21].…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations